Caroperla longiseta (Plecoptera: Perlidae), a new stonefly species from Thailand - Sivec, Ignac (Illiesia, 2010)
Caroperla longiseta sp. nov., is described from adult and larval specimens collected in Chiang Mai Province, Thailand. The new species is compared to C. pacifica Kohno, the only previously known member of the genus.
Keywords: Caroperla; entomology; new species; Perlidae; Plecoptera; Thailand